The issue of using colloquial dialect while teaching Arabic language courses in schools and universities in the Kingdom of Saudi Arabia - Al-Awaidi, Wafa Hafez; Al-Ahmadi, Ebtehal Yahya (Journal of Educational and Psychological Sciences, 2020)
The study targeted decisiveness in the issue of using colloquial dialect during teaching the Arabic language courses in schools and universities in the Kingdom of Saudi Arabia and to achieve the goal of the study using researchers the descriptive survey method and an electronic questionnaire was designed and enabled the integrity of questions linguistically and then it was published in the educational community and the study community may be from all The teachers of the Arabic language in the Kingdom of Saudi Arabia who are participants in the questionnaires (5,100) individuals, then the opinions were statistically addressed using percentages and extending the inventory of the percentage of supporters and opponents and the reasons for each team, and the election period in favor of the opponents Yen Bin Baba (68.63), and one of the main reasons for the opposition is the necessity of preserving classical Arabic, which is the language of the Holy Qur’an, and that the use of colloquial language impedes students from using classical soundly and impedes their understanding of the Arabic language. Concerning the percentage of supporters (31.37), one of the most important reasons for their support is because students use colloquiality in their daily lives so they are accustomed to hearing it, and it helps to understand some meanings and the arrival of the information.